2012
DOI: 10.5966/sctm.2011-0029
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Skin and Wound Fibroblast Migration by Mesenchymal Stem Cells Derived from Normal Donors and Chronic Wound Patients

Abstract: Chronic wounds continue to be a major cause of morbidity for patients and an economic burden on the health care system. Novel therapeutic approaches to improved wound healing will need, however, to address cellular changes induced by a number of systemic comorbidities seen in chronic wound patients, such as diabetes, chronic renal failure, and arterial or venous insufficiency. These effects likely include impaired inflammatory cell migration, reduced growth factor production, and poor tissue remodeling. The mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 37 publications
0
66
1
1
Order By: Relevance
“…Experiments utilizing MSC-conditioned media have demonstrated the importance of the paracrine mechanism of BM-MSC-induced wound healing [49][50][51][52]. More recent work in our laboratory has demonstrated that MSCs could enhance fibroblast migration without cell contact in a dosedependent manner [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments utilizing MSC-conditioned media have demonstrated the importance of the paracrine mechanism of BM-MSC-induced wound healing [49][50][51][52]. More recent work in our laboratory has demonstrated that MSCs could enhance fibroblast migration without cell contact in a dosedependent manner [19].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived MSCs have been shown to be efficacious in the treatment of wounds, including chronic wounds [14,18,19]. Previous work in our laboratory has demonstrated that bone marrow-derived cells play an important role in cutaneous wound healing and that direct application of bone marrow-derived cells to patients with chronic nonhealing wounds leads to wound closure and dermal rebuilding [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chronic wound patients, such as patients with diabetes, chronic renal failure, and arterial or venous insufficiency, these effects likely include impaired inflammatory cell migration, reduced growth factor production, and poor tissue remodeling. Rodriguez-Menocal et al [58] studied fibroblasts derived from normal donors and chronic wound patients that were co-cultured after an in vitro scratch assay. They found that the migration ability was significantly reduced in the fibroblast treatment of BM-MSCs from chronic wound patients compared to MSCs from normal donors.…”
Section: Disease Microenvironmentmentioning
confidence: 99%